2020
DOI: 10.1080/08870446.2020.1836180
|View full text |Cite
|
Sign up to set email alerts
|

Symptom appraisal in uncertainty: a theory-driven thematic analysis with survivors of childhood cancer

Abstract: Objective: Somatic symptoms capture attention, demand interpretation, and promote health behaviors. Symptom appraisal is particularly impactful within uncertain health contexts such as cancer survivorship. Yet, little is known about how individuals make sense of somatic symptoms within uncertain health contexts, nor how this process guides health behaviors.Design: 25 adolescent and young adult survivors of childhood cancer completed semi-structured interviews regarding how they appraise and respond to changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…These risks do not go unnoticed by survivors of childhood cancer (SCCs). Qualitative studies have indicated that SCCs are vigilant for and worry about somatic symptoms such as aches and pains, fatigue, and dyspnea as signs of recurrent cancer, even when those symptoms have a benign cause 3,4 . Pain has been identified as a particularly common source of worry; however a wide variety of somatic symptoms appear to trigger cancer‐related concerns.…”
Section: Introductionmentioning
confidence: 99%
“…These risks do not go unnoticed by survivors of childhood cancer (SCCs). Qualitative studies have indicated that SCCs are vigilant for and worry about somatic symptoms such as aches and pains, fatigue, and dyspnea as signs of recurrent cancer, even when those symptoms have a benign cause 3,4 . Pain has been identified as a particularly common source of worry; however a wide variety of somatic symptoms appear to trigger cancer‐related concerns.…”
Section: Introductionmentioning
confidence: 99%
“…During initial analysis, codes were generated inductively. Following reviewers' feedback, the data were re-analysed using a hybrid inductive-deductive approach [21,28] to deepen the analysis; this was appropriate as treatment was informed by the psychological flexibility model [29]. Codes for "openness", "awareness", and "engagement" --key facets of psychological flexibility [22] --were deductively applied.…”
Section: Discussionmentioning
confidence: 99%
“…The two interviewers (PhD and Masters level research psychologists; both female) did not have previous experience of conducting semi‐structured interviews but had received training and supervision in qualitative research methods. Participant inclusion criteria, consent information, and the full semi‐structured interview procedure are described elsewhere 4 . The study protocol was approved by the Stanford Medicine Institutional Review Board (IRB‐44463).…”
Section: Methodsmentioning
confidence: 99%